(untitled) (Journal of Science and Technology, 2016)
The indigenous architecture of Northern Ghana is unique and different from that of the southern regions of the country. It has grown out of the hot dry climatic conditions and limited resources of this savanna country. This paper appraises the resourcefulness and skills of the builders in the use of the available building materials’-laterite and thatch - especially the technique of mural decoration which is an important dimension of the art of building in this region. It considers the decorations as a language with a vocabulary of lines and textures which apparently speak of the life in this region.